Manajemen Sumber Daya Manusia Dalam Meningkatkan Pelayanan Nasabah Di Pt Bank Bni Kecamatan Somba Opu Kabupaten Gowa - Riskiani, Riskiani; Madani, Muhlis; Tahir, Nurbiah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
This research aims to analyze human resource management in supporting service improvement. The research method used is descriptive qualitative. Data was collected through interviews, documentation and media review. The research results show that. The work assignment indicator shows that the work assignment in improving customer service at PT Bank BNI Gowa Branch has been carried out quite well, the work quality indicator can be concluded that BNI Gowa Branch customers are satisfied with the products, promotions and services provided in accordance with customer expectations, the quantity indicator shows that transactions at Bank BNI Gowa Branch are quite fast and good, the timeliness indicator shows that work is always carried out on time, then the utilization of time used by each employee is currently quite good, and the cost effectiveness indicator shows that BNI Branch employees Gowa has been quite effective in maximizing standard guidelines when transacting with customer.